International society of sport psychology position stand: Athletes` mental health, performance, and development - Schinke, R. J.; Stambulova, N. B.; Si, G.; Moore, Z. (International Journal of Sport and Exercise Psychology, 2018)
Mental health is a major resource for athletes in relation to their performance and development. Concurrently, athletes experience additional mental health risk factors compared to non-athletic population, such as high training loads, tough competitions, and a stressful lifestyle. Contemporary statistics demonstrate a substantial growth in athletes` mental health-related problems, such as concussion, overtraining, and identity crisis. Therefore, the International Society of Sport Psychology through this Position Stand provides support to sport psychology researchers, practitioners, sport participants, and stakeholders in understanding: (a) mental health phenomenon based on continuum-type models outlining mental illness (prevalence vs. absence) and mental health in association with peak performance, (b) major findings of research dealing with athletes` performance, career and personal (e.g. identity) development in relation to mental health issues, and (c) interventions aimed at monitoring and maintaining athletes` mental health as well as preventing various forms of mental ill-being. Five major sections reflect the logic outlined above (i.e. from definitions and theories to research and practice), complemented by 10 postulates summarising the International Society of Sport Psychology message intended to spur further discussions on how to make athletes healthier and, thus, more resourceful for (and through) sport.